Hemorrhagic Meckel’s diverticulum in an older woman diagnosed by repeated angiographies - Jee Suk LEE; Won Moon; Seun Ja PARK; Moo In PARK; Kyu Jong KIM; Sang Ho LEE; Hee Kyung Chang; Gyu Sik JUNG (Turkish Journal of Gastroenterology, 2019)
-